1991
DOI: 10.1254/jjp.57.175
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Relaxing Effects and β2-Selectivity of TA-2005, a Newly Developed Bronchodilating Agent, in Isolated Guinea Pig Tissues

Abstract: ABSTRACT-Tracheal relaxing effects and /32-selectivity of TA-2005 were investi gated by functional experiments and radioligand binding assay in guinea pigs in com parison with those of other ,Q-agonists, isoproterenol, procaterol, formoterol and sal butamol. The relaxing activity of TA-2005 on histamine-induced contraction in the isolated trachea was most potent among the five agonists, and it was blocked by a 82 selective antagonist (ICI 118,551) but not by a /3,-selective antagonist (bisoprolol). The potency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 17 publications
3
25
0
1
Order By: Relevance
“…Moreover, it displays a fast onset and long duration of activity under both in vitro and in vivo experimental conditions (Kikkawa et al, 1991(Kikkawa et al, , 1994Voss et al, 1992). It is noteworthy that the persistence of action of carmoterol at human recombinant ␤ 2 -ARs is similar to that of salmeterol, and longer than that of indacaterol, which is longer than that of formoterol (Summerhill et al, 2008).…”
Section: Ultra-long-acting ␤ 2 -Adrenergic Receptor Agonistsmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, it displays a fast onset and long duration of activity under both in vitro and in vivo experimental conditions (Kikkawa et al, 1991(Kikkawa et al, , 1994Voss et al, 1992). It is noteworthy that the persistence of action of carmoterol at human recombinant ␤ 2 -ARs is similar to that of salmeterol, and longer than that of indacaterol, which is longer than that of formoterol (Summerhill et al, 2008).…”
Section: Ultra-long-acting ␤ 2 -Adrenergic Receptor Agonistsmentioning
confidence: 97%
“…Carmoterol. Carmoterol (CHF 4226, TA 2005), a pure R,R-isomer, is a noncatechol ␤ 2 -agonist with a pmethoxyphenyl group on the amine side chain and a 8-hydroxyl group on the carbostyril aromatic ring (Kikkawa et al, 1991), possesses structural elements from both formoterol and procaterol, and binds very firmly to ␤ 2 -ARs (Voss et al, 1992), a property shared by some other agonists that, like carmoterol, are based on a carbostyril skeleton (Standifer et al, 1989). In studies employing chimeric ␤ 2 -ARs, the methoxyphenyl group in carmoterol has been found to be critical to the ␤ 2 -AR selectivity of the molecule (Kikkawa et al, 1998).…”
Section: Ultra-long-acting ␤ 2 -Adrenergic Receptor Agonistsmentioning
confidence: 99%
“…Прием всех исследованных дозировок вилантерола сопровождался низкой частотой побоч ных эффектов [39]. Кармотерол -чистый R,R изомер -некатехолами новый агонист β 2 АР с р метоксифенильной груп пой на аминовой боковой цепи и 8 гидроксильной группой на карбостириловом ароматическом коль це [40]. Он несет в своем строении структурные эле менты как формотерола, так и прокатерола, и очень Новое о лекарственных препаратах прочно связывается с β2 АР [41].…”
Section: новое о лекарственных препаратахunclassified
“…Carmoterol (CHF 4226; TA 2005), a noncatechol b 2 -adrenoceptor agonist with a p-methoxyphenyl group on the amino side chain and a 8-hydroxyl group on the carbostyril aromatic ring [27], possessing structural elements from both formoterol and procaterol, binds very firmly to the b 2 -adrenoceptor [28]. Carmoterol displays a fast onset and long duration of activity under both in vitro and in vivo experimental conditions [27][28][29].…”
Section: Carmoterolmentioning
confidence: 99%
“…Carmoterol displays a fast onset and long duration of activity under both in vitro and in vivo experimental conditions [27][28][29]. Carmoterol is in development by Chiesi Farmaceutici (Parma, Italy), under license from Tanabe Seiyaku Co. (Saitama, Japan).…”
Section: Carmoterolmentioning
confidence: 99%